Artificial sweeteners and risk of cardiovascular diseases: results from the prospective NutriNet-Santé cohort. (7th September 2022) - Debras, Charlotte; Chazelas, Eloi; Sellem, Laury; Porcher, Raphaël; Druesne-Pecollo, Nathalie; Esseddik, Younes; de Edelenyi, Fabien Szabo; Agaësse, Cédric; De Sa, Alexandre; Lutchia, Rebecca; Fezeu, Léopold K; Julia, Chantal; et al.
Abstract: Objectives: To study the associations between artificial sweeteners from all dietary sources (beverages, but also table top sweeteners, dairy products, etc), overall and by molecule (aspartame, acesulfame potassium, and sucralose), and risk of cardiovascular diseases (overall, coronary heart disease, and cerebrovascular disease). Design: Population based prospective cohort study (2009-21). Setting: France, primary prevention research. Participants: 103 388 participants of the web based NutriNet-Santé cohort (mean age 42.2±14.4, 79.8% female, 904 206 person years). Dietary intakes and consumption of artificial sweeteners were assessed by repeated 24 h dietary records, including brand names of industrial products. Main outcomes measures: Associations between sweeteners (coded as a continuous variable, log10 transformed) and cardiovascular disease risk, assessed by multivariable adjusted Cox hazard models. Results: Total artificial sweetener intake was associated with increased risk of cardiovascular diseases (1502 events, hazard ratio 1.09, 95% confidence interval 1.01 to 1.18, P=0.03); absolute incidence rate in higher consumers (above the sex specific median) and non-consumers was 346 and 314 per 100 000 person years, respectively. Artificial sweeteners were more particularly associated with cerebrovascular disease risk (777 events, 1.18, 1.06 to 1.31, P=0.002; incidence rates 195 and 150 per 100 000 person years in higher and non-consumers, respectively). Aspartame intake was associated with increased risk of cerebrovascular events (1.17, 1.03 to 1.33, P=0.02; incidence rates 186 and 151 per 100 000 person years in higher and non-consumers, respectively), and acesulfame potassium and sucralose were associated with increased coronary heart disease risk (730 events; acesulfame potassium: 1.40, 1.06 to 1.84, P=0.02; incidence rates 167 and 164; sucralose: 1.31, 1.00 to 1.71, P=0.05; incidence rates 271 and 161). Conclusions: The findings from this large scale prospective cohort study suggest a potential direct association between higher artificial sweetener consumption (especially aspartame, acesulfame potassium, and sucralose) and increased cardiovascular disease risk. Artificial sweeteners are present in thousands of food and beverage brands worldwide, however they remain a controversial topic and are currently being re-evaluated by the European Food Safety Authority, the World Health Organization, and other health agencies. Trial registration: ClinicalTrials.gov NCT03335644